The Relevance of The Independent Learning Curriculum to the 21st Century Learning Model in Development of Society Era 5.0 - Limbong, Ezra Egidia Shelomita; Pasaribu, Shofia Debora; Tampubolon, Yenji Betaria Sonata; Lubis, Rajo Hasim (Lembaga Riset Mutiara Akbar, 2024)
Society 5.0 is a society that can solve various social challenges and problems by utilizing various innovations that were born in the era of the industrial revolution 4.0, such as the internet of things (internet for everything), artificial intelligence (artificial intelligence), Bit Data (large amounts of data), and robots to improve the quality of human life. This era is a new opportunity and challenge for students to improve their soft skills as preparation for the future. It is generally known that the curriculum is the